2021
DOI: 10.1016/j.nicl.2021.102832
|View full text |Cite|
|
Sign up to set email alerts
|

Contributions of childhood abuse and neglect to reward neural substrates in adolescence

Abstract: Highlights Relative and interactive effects of abuse and neglect were examined. Abuse was linked with altered activation in threat- and emotion-related regions. Youths with both high abuse and neglect showed qualitatively different patterns. The effects of childhood adversity may not necessarily be additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…50 Sixth, ACEs can affect brain development and function, including brain's reward system, making children more prone to seeking out substances to experience pleasure or relief. 51 Finally, substance use can perpetuate a cycle of adverse experiences, as it can lead to criminal behaviors, legal problems, and further adverse events, creating a negative feedback loop. 52 Early identification of these mechanisms as well as substance use initiation patterns can help develop early interventions, access to mental health services, supportive relationships, and resiliencebuilding strategies for children to cope with their experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Sixth, ACEs can affect brain development and function, including brain's reward system, making children more prone to seeking out substances to experience pleasure or relief. 51 Finally, substance use can perpetuate a cycle of adverse experiences, as it can lead to criminal behaviors, legal problems, and further adverse events, creating a negative feedback loop. 52 Early identification of these mechanisms as well as substance use initiation patterns can help develop early interventions, access to mental health services, supportive relationships, and resiliencebuilding strategies for children to cope with their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, children who have experienced ACEs may be more vulnerable to peer pressure and external influences, including associations with peers who use substances 50 . Sixth, ACEs can affect brain development and function, including brain's reward system, making children more prone to seeking out substances to experience pleasure or relief 51 . Finally, substance use can perpetuate a cycle of adverse experiences, as it can lead to criminal behaviors, legal problems, and further adverse events, creating a negative feedback loop 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these deficits may cause more social withdrawal and limited interpersonal relationships, which further decrease interest in caring for others ( Music, 2011 ). Additionally, some studies have found that neglect predicts the hyposensitivity of reward and blunted reward processing ( Bounoua et al, 2021 ; Yang et al, 2021 ). In this case, children who have experienced neglect would be less likely to associate prosocial behavior with positive social consequences (such as obtaining social reward or a good reputation or avoiding social punishment), which would in turn reduce the willingness to engage in prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Monetary incentive delay task ( Birn et al, 2017 ; Boecker-Schlier et al, 2016 ; DelDonno et al, 2019 ; Dennison et al, 2016 ; Dennison et al, 2019 ; Dillon et al, 2009 ; Hendrikse et al, 2022 ; Mehta et al, 2010 ; Morelli et al, 2021 ; Sheridan et al, 2018 ; Yang et al, 2021 )…”
Section: Methodsmentioning
confidence: 99%